Oxford Student's Dictionary of English.
The Oxford student's dictionary shows you, using a defining vocabulary of 2500 words, how to use the common words of English and helps you build your vocabulary by introducing you to related words. 40 study pages offer advice and practice in preparing for exams, writing letters, essays, and reports, analysing graphs and taking notes. This dictionary explains in simple English the words you need to be able to understand more difficult or specialist texts.